Characterization and classification of saline/sodic soils of Coba area of non-irrigated farmlands in Golina Watershed in Raya Valley, Amhara Region, Ethiopia - mengesha, merse; W, Lemma; Solomon, T (Food, Agriculture and Natural Resources - NETWORKS, 2024)
The soil in the Coba area of the Golina watershed at Raya Kobo Valley contains various soluble salts and exchangeable sodium, magnesium, potassium, and calcium. However, excessive concentrations of these elements can affect soil processes and plant growth, with the impact varying based on concentration levels and plant types. To study the salt-affected soils in the area, we excavated one profile from non-irrigated fields and collected ten soil samples at 20 cm intervals in a two-meter profile. The samples were analyzed for chemical properties such as pH, soluble cations and anions, electrical conductivity, exchangeable cations (Ca, Mg, Na, and K), total nitrogen, organic carbon, available phosphorus, exchangeable sodium percentage, sodium absorption ratio, as well as physical characteristics such as soil color, texture, bulk density, and porosity. The analysis revealed that the non-irrigated soil profile had a pH of 7.4 to 8.5, electrical conductivity of 3.1 to 9.7 dsm-1, organic carbon of 0.4 to 1.5%, total nitrogen of 0.09 to 0.27%, available phosphorus of 25 to 46.5 mg kg-1, and a cation exchange capacity of 48.7 to 57.2 cmol (+) kg-1. Considering the top layers of the soil responsible for agricultural purposes, the electrical conductivity, exchangeable sodium percentage, and pH values indicate that the soil can be classified as saline-sodic soil for non-irrigated farmland.